A Coupled Nonlinear Flow Model for Particle Migration and Seepage Properties of Water Inrush through Broken Rock Mass. (9th September 2020) - Shi, Wenhao; Yang, Tianhong
Abstract : A large number of statistics indicate that broken rock mass always transforms into a flowing channel and leads to water inrush disasters in mining engineering, such as fault, karst, and strongly weathered rock mass. During the process of water inrush, the structure of the broken rock mass is constantly changing due to seepage erosion under high-velocity flow. Therefore, it is of vital importance to quantitatively evaluate the flow behavior of the water inrush related to the seepage erosion in order to prevent or reduce the risks. This study described a coupled nonlinear flow model, which couples the high-velocity seepage, the small particle migration, and the evolution of the broken rock mass structure. The model was verified firstly for simulation of nonlinear flow behavior by comparing with the traditional one. Then, the proposed model was used to simulate the evolution of particle migration and seepage properties of the water inrush through broken rock mass by a numerical case. The simulation results generally agree well with the existing experimental results. The simulations indicate that small particle migration causes the unstable characteristics of the seepage and the heterogeneity properties of the broken rock mass, which lead to the nonlinear flow behavior of the water inrush in both time and space. From a different perspective, it also indicates that the proposed model is capable of simulating the interaction of high-velocity seepage, small particle migration, and evolution of broken rock mass structure in the process of water inrush.